Who's saying what in Jamestown, Thomas Savage? - Fritz, Jean (G. P. Putnam's Sons, 2007)
A biography of Thomas Savage, one of the early colonists of Jamestown, Virginia, who was sent to live among the Indians in order to learn their language and become an interpreter.